2021
DOI: 10.1007/s11010-021-04056-x
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase inhibitor hydroxyfasudil protects against HIV-1 Tat-induced dysfunction of tight junction and neprilysin/Aβ transfer receptor expression in mouse brain microvessels

Abstract: HIV-1 transactivator protein (Tat) induces tight junction (TJ) dysfunction and amyloid-beta (Aβ) clearance dysfunction, contributing to the development and progression of HIV-1-associated neurocognitive disorder (HAND). The Rho/ROCK signaling pathway has protective effects on neurodegenerative disease. However, the underlying mechanisms of whether Rho/ROCK protects against HIV-1 Tat-caused dysfunction of TJ and neprilysin (NEP)/Aβ transfer receptor expression have not been elucidated. C57BL/6 mice were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…First, the HIV-1 transactivator of transcription (tat) and envelope glycoprotein gp120 (gp120) may promote the synthesis, secretion, and accumulation of β-amyloid [23,39]. Second, tat and/or tat-derived peptides may inhibit neprilysin [39,41,42], a key enzyme for β-amyloid degradation [43]. In addition, it is well-recognized that the blood-brain barrier (BBB) is compromised by HIV-1 viral proteins (for review, [44]); dysfunction which may influence β-amyloid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…First, the HIV-1 transactivator of transcription (tat) and envelope glycoprotein gp120 (gp120) may promote the synthesis, secretion, and accumulation of β-amyloid [23,39]. Second, tat and/or tat-derived peptides may inhibit neprilysin [39,41,42], a key enzyme for β-amyloid degradation [43]. In addition, it is well-recognized that the blood-brain barrier (BBB) is compromised by HIV-1 viral proteins (for review, [44]); dysfunction which may influence β-amyloid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mitochondrial damage, RAGE contributes to aortic structural changes characterized by increased collagen deposition in rodents [ 108 , 112 ]. Recent studies have indicated that HIV-1 Tat-induced RAGE expression within the blood–brain barrier accelerates amyloid beta deposition [ 36 , 37 , 38 ]. The influence of RAGE within the heart could also be an underlying mechanism for Tat-induced CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tat induces bradycardia by activating parasympathetic neurons within the nucleus ambiguous [ 35 ] and mediates vascular aging in rodents [ 30 ]. Although the Tat-mediated mechanisms that may contribute to CVDs are not well understood, Tat has been demonstrated to upregulate the receptor for advanced glycation end products (RAGE) within the blood-brain barrier [ 36 , 37 , 38 ], a receptor target known to be involved in CVD [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TLR3 is activated by the dsRNA analog, polyinosinic:polycytidylic acid (poly[I:C]) (Hanke & Kielian, 2011). New evidence indicates the role of viruses, including human herpes virus (HSV) 1, 6A, and 7, and hepatitis B viruses, in the pathology of Alzheimer's disease (AD) (Chen et al, 2021; Civitelli et al, 2015; Mastroeni et al, 2018; Readhead et al, 2018). HSV‐1‐infected neuron inactivates neprilysin (NEP) and glycogen synthase kinase 3β, whose products are involved in Aβ clearance and tau phosphorylation, respectively (Civitelli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…HSV‐1‐infected neuron inactivates neprilysin (NEP) and glycogen synthase kinase 3β, whose products are involved in Aβ clearance and tau phosphorylation, respectively (Civitelli et al, 2015). Human immunodeficiency virus (HIV) 1 transactivator protein induces Aβ clearance dysfunction through decreased NEP protein levels (Chen et al, 2021). The extracellular Aβ levels increase through lower NEP expression coupled with a significant decrease in its activity in primary cultures of HIV‐1 infected astrocytes (Martínez‐Bonet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%